2023
DOI: 10.1029/2021rg000763
|View full text |Cite
|
Sign up to set email alerts
|

Health and Safety Effects of Airborne Soil Dust in the Americas and Beyond

Abstract: Risks associated with dust hazards are often underappreciated, a gap between the knowledge pool and public awareness that can be costly for impacted communities. This study reviews the emission sources and chemical, physical, and biological characteristics of airborne soil particles (dust) and their effects on human and environmental health and safety in the Pan‐American region. American dust originates from both local sources (western United States, northern Mexico, Peru, Bolivia, Chile, and Argentina) and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 598 publications
(893 reference statements)
1
10
0
Order By: Relevance
“…Future research also needs to complement metagenomically identified bacteria and fungi by monitoring culturability to better assess microorganisms’ role in ecosystem, human, plant, and animal health. ,,,, Such studies should also measure other water-soluble aerosol components and metal speciation, some of which might affect viability. Additionally, airborne pollutants have the capacity to influence aerobiome abundance, diversity, transport, and deposition, and conversely, bioaerosols can facilitate the transport and deposition of airborne pollutants. , The interplay between bioaerosols and anthropogenic emissions is complex and dependent on multiple factors, including pollutant type, concentration levels, and meteorological parameters.…”
Section: Implications and Future Workmentioning
confidence: 99%
“…Future research also needs to complement metagenomically identified bacteria and fungi by monitoring culturability to better assess microorganisms’ role in ecosystem, human, plant, and animal health. ,,,, Such studies should also measure other water-soluble aerosol components and metal speciation, some of which might affect viability. Additionally, airborne pollutants have the capacity to influence aerobiome abundance, diversity, transport, and deposition, and conversely, bioaerosols can facilitate the transport and deposition of airborne pollutants. , The interplay between bioaerosols and anthropogenic emissions is complex and dependent on multiple factors, including pollutant type, concentration levels, and meteorological parameters.…”
Section: Implications and Future Workmentioning
confidence: 99%
“…Heterotrophic microbes were detected in the burned soil samples with the phyla Actinobacteria , Firmicutes , and Protobacteria notably being enriched postfire (Figures E and S7A). These phyla contain heterotrophic species that could likely metabolize SOM in burned soils. ,, Other bacterial genera known to possess putative beneficial traits for the postfire ecosystem such as Geobacillus (spore formation) and Kocuria (distribution via dust or smoke) were also identified as discriminant taxa for burned soils (Figure G).…”
Section: Results and Discussionmentioning
confidence: 99%
“…These phyla contain heterotrophic species that could likely metabolize SOM in burned soils. 12,17,96 Other bacterial genera known to possess putative beneficial traits for the postfire ecosystem such as Geobacillus (spore formation) 97 and Kocuria (distribution via dust or smoke) 98 were also identified as discriminant taxa for burned soils (Figure 1G).…”
Section: Gas Chromatography−mass Spectrometry (Gc-ms)mentioning
confidence: 99%
“…Wind erosion and resultant blowing dust are important threats to ecosystems and human health in the Chihuahuan Desert of New Mexico (Figure 4). Wind erosion selectively removes fine soil, nutrients, and carbon (Webb et al, 2012), while blowing dust exposure is linked to adverse health effects such as asthma, Valley fever infections, and is a safety hazard to road transportation (Tong et al, 2023). Ecologically, the region is dominated by grasslands and savannas, which have experienced extensive shrub encroachment and loss of perennial grasses that are desirable for livestock production (Bestelmeyer et al, 2018).…”
Section: Case Study: Assessing Wind Erosion Risk In the Chihuahuan De...mentioning
confidence: 99%